Hybrid graphene oxide/crumpled graphene film via subcooled boiling-induced self-assembly for highly efficient boiling heat transfer. (December 2021) - Chu, Ben; Fang, Cheng; Zheng, Feiyu; Cheng, Weizheng; Wang, Ruitong; Zhang, Wanli; Tao, Jinran; Huai, Lei; Tao, Peng; Song, Chengyi; Shang, Wen; Fu, Benwei; et al.
Abstract: Graphene-based films generated on a substrate can modify surface structure and chemistry to enable the improvement in heat transfer capacity for many important boiling-related applications. Current methods for preparing these films, however, require additional processing equipment and involve relatively complex processes. Achieving simple and controllable generation of these films remains a great challenge. In this work, we develop a facile subcooled boiling-induced self-assembly (SBISA) method for generating graphene-based films. We first explore the SBISA mechanism and demonstrate the formation of graphene-based films under the action of a combined force induced by the capillary pressure, structural disjoining pressure, and vapor recoil force. In addition, using the SBISA process, we generate a tunable hybrid graphene oxide (GO)/crumpled graphene (CG) film with mixed wettability. The hybrid GO/CG film enables large performance enhancements for boiling with a 150.0% increase in the critical heat flux (CHF) and a 163.9% increase in the maximum heat transfer coefficient (HTC) over a pristine copper surface. This SBISA strategy provides an alternative approach for fabricating tunable films with a hierarchical structure and mixed wettability on various substrates, and it may also help produce surfaces with different micro/nanostructures for enhancing phase-change-based heat transfer. Graphical abstract: Image 1 Highlights: We developed a facile subcooled boiling-induced self-assembly (SBISA) method to generate a hybrid GO/CG film. We first explored the mechanism of the SBISA of different graphene-based materials. The hybrid GO/CG film showed a micro/nanostructure and mixed wettability. The hybrid GO/CG film enabled a remarkable performance enhancement with a CHF of 2, 270.1 kW/m 2 and a maximum HTC of 120.35 kW/m 2 /K.